Analisis Kepemimpinan Kepala Sekolah yang Ideal di Abad 21: Studi Literatur - Salwa Ghaida Rakhmawati; Siti Nuraeni Azzahro; Linda Setiawati; Lutfi Khoerunnisa (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
In line with the rapid development of the times, both in the fields of knowledge and technology, the role of leaders must be alert and understand new things in order to be able to provide innovation for the running of an organization. School principals have an important role in moving teachers, staff and students to follow changing developments in the 21st century. This research aims to determine the role and strategies of school principals in leading schools effectively in the 21st century, find out what competencies and characteristics school principals must have in leading schools in the 21st century, and find out the challenges faced by school principals in implementing their leadership in the 21st century. This research uses a qualitative method with a literature study approach. Data sources were taken from various relevant articles discussing leadership in general and leadership in the school environment. The results of the analysis show that the principal as a leader must have an attitude and character that reflects the spirit of a firm leader and can bring about significant development of school culture. With the role of the school principal as a driving force, it is hoped that changes can be made for schools in terms of teacher professionalism, learning curriculum, and students' abilities towards 21st century learning. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.